Engineering synucleinopathy-resistant human dopaminergic neurons by CRISPR-mediated mutation of the SNCA gene - Chen, Yixi (The University of Edinburgh, 2020)
An experimental treatment for Parkinson’s disease (PD) involved the transplantation of fetal midbrain tissue, a source of midbrain dopaminergic (mDA) progenitors, into the striatum of patients to restore dopaminergic innervation. Although clinical benefits were experienced by some patients, this heterogeneous and scarce source of tissue is not sustainable. Recently, mDA progenitors differentiated from human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs) are comparably potent and efficient as fetal midbrain tissue in rescuing dopaminergic deficits in PD animal models and clinical trials using this cell product are progressing. However, the hESC/hiPSC-derived mDA grafts are still susceptible to the development of Lewy body pathology, as found in clinical trials using fetal tissues. The clinical benefits of the fetal grafts reduced in correlation with the accumulation of Lewy body pathology, therefore, a pathology-resistant graft would be longer-lasting and beneficial to patients. For in vitro modelling of Lewy body pathology, which is an inclusion pathology mainly consist of misfolded α-Synuclein (α-Syn) aggregates, I treated hESC-derived mDA neurons with α-Syn pre-formed fibrils (PFFs). PFFs recruit endogenous α-Syn to form Lewy body-like aggregates which are positive for phospho-serine 129 α-Syn (pS129-αSyn), ubiquitin and p62. The PFF models also recapitulate other aspects of PD, such as synaptic and mitochondrial dysfunction, neuroinflammation and neurodegeneration. Since endogenous α-Syn is essential for the development of aggregates, I attempted to produce pathology-resistant neurons by knocking out α-Syn (SNCA) in hESCs with CRISPR/Cas9n and subsequently differentiating the SNCA+/– and SNCA–/– hESCs into mDA neurons. As α-Syn might play physiological roles which are not yet fully elucidated, I created a single amino acid (S87E) mutation in α-Syn, aiming to reduce α-Syn aggregation without disruption of α-Syn physiological functions. Half of the resulting CRISPR-engineered SNCA+/–, SNCA–/– and SNCAS87E/S87E hESC clones exhibited normal genomic integrity, free from detectable copy number variations (CNVs), large copy-neutral loss of heterozygosity (CN-LOH), off-target events and integration of targeting plasmids. Subsequently, mDA neurons were differentiated from SNCA+/–, SNCA–/– and SNCAS87E/S87E hESCs and they highly resembled mDA neurons derived from WT parental hESCs based on marker analysis and RNAseq. This data suggested that the α-Syn mutations, as well as the selection and cloning process, did not impair mDA differentiation. Synapse formation, spontaneous activities and dopamine secretion were readily observed in mDA neurons of all tested genotypes. The WT mDA neurons treated with PFFs recapitulated pS129-αSyn pathology, but did not result in detectable cell death or significant impairment of synapse formation, mitochondrial morphology or spontaneous neuronal activities within the timeframe of the current study. SNCA+/–, SNCA–/– and SNCAS87E/S87E mDA neurons treated with PFFs revealed that SNCA+/– exhibited significantly less, while SNCA–/– showed no pS129-αSyn pathology and SNCAS87E/S87E exhibited a reduced level of pathology compared to WT mDA neurons. The PFF-treated hESC-derived mDA neuron model established in this study could be used as an effective platform for drug screening. In addition, SNCA+/– and SNCA–/– hESC-derived cells could be valuable cell models for studying the physiological role of α-Syn. On the condition of satisfactory validation in animal models, SNCA+/– and SNCA–/– hESC-derived mDA progenitors would have significant potential in cell replacement therapy for PD.
Keywords: Parkinson’s disease; cell replacement therapy; midbrain dopaminergic progenitors; mDA; Lewy body; α-Synuclein; α-Syn